PENGEMBANGAN BAHAN AJAR E-COMIC BERBANTUAN CANVA PADA MATA PELAJARAN BAHASA INDONESIA KELAS III SDN 58/II SARI MULYA - Ria Setiawati; Saputra, Agus; Kharisna, Feby (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This research is motivated by the difficulties of students in understanding learning materials, especially in Indonesian Language subjects, due to the lack of innovative teaching materials used, wich are still in printed form and based on textbooks. The purpose of this research is to produce e-comic teaching mterials assisted by Canva in Indonesian Language subject that are valis, practical, effective. The research method used is the Research and Development (R&D) method. The development model used is the ADDIE model, wich consists of five stages: analysis, design, development, implementation, and evaluation. The validation result of teaching materials assisted by Canva in Indonesian Language subject were validated by five validators, with the following result: language aspect 87,5% with very valid category, graphic design expert validation 88,3% with very valid category, learning module expert validation 90%, question expert validation 88,8% with very valid category, and material expert validation 86,9% with very valid category. The result of the analysis of educator response qestionnaires obtained 100% with very practical category and student response questionnaires 94,6% with veri practical category. In the effectiveness test, an average score of 90% was obtained with a very effective category.